Gas sensor and powder for gas sensor

By adjusting the distribution of Y2O3/(ZrO2+Y2O3) mol% in the solid electrolyte of the gas sensor, a reasonable proportion of stable and unstable areas is formed, the problem of decrease in intensity during hot and cold cycles is solved, and the stability of the gas sensor is improved and performance.

CN114746747BActive Publication Date: 2025-02-14DENSO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080084147.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-04
Filing Date
2020-11-17
Publication Date
2025-02-14
Estimated Expiration
2040-11-17

AI Technical Summary

Technical Problem

The solid electrolytes in existing gas sensors are prone to decrease in strength during hot and cold cycles, mainly due to stress and volume changes caused by phase change of unstable phases.

Method used

By adjusting the distribution of Y2O3/(ZrO2+Y2O3) mol% in the cross section of the solid electrolyte, the area ratio of the area in the region above 3.5 mol% and below 6.9 mol% reaches more than 10%, forming a reasonable way to achieve stable and unstable areas To suppress the decrease in intensity caused by cold and heat cycles.

Benefits of technology

It effectively suppresses the decrease in the strength of solid electrolyte caused by the hot and cold cycle, and improves the stability and performance of the gas sensor under high temperature and cooling cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114746747B_ABST
    Figure CN114746747B_ABST
Patent Text Reader

Abstract

A gas sensor (1) comprises a solid electrolyte (21) made of zirconium oxide containing yttria. In the solid electrolyte (21), the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 in the entire cross section of the solid electrolyte (21) is 3.5 mol% or more and 6.9 mol% or less. With respect to the solid electrolyte (21), when in the cross section of the solid electrolyte (21), the area ratio of a region (211) in which the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 is 3.3 mol% or less relative to the entire cross section is set to A%, and the area ratio of a region (212) in which the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 is 7 mol% or more relative to the entire cross section is set to B%, the total of A and B, i.e., the total area ratio (A+B), is 10% or more.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is based on Japanese Patent Application No. 2019-219911 filed on December 4, 2019, and the contents thereof are cited herein. Technical Field

[0002] The present disclosure relates to a gas sensor and powder for a gas sensor. Background Art

[0003] Conventionally, a gas sensor is installed in the exhaust pipe of an engine in a car to detect a specific gas in the exhaust gas. As such a gas sensor, a gas sensor having a solid electrolyte composed of zirconium oxide (ZrO2) containing yttrium oxide (Y2O3) is known.

[0004] For example, Patent Document 1 discloses an oxygen sensor having a ZrO2-Y2O3 solid electrolyte having an X-ray diffraction intensity ratio of specific faces of a monoclinic crystal (hereinafter sometimes referred to as an M phase) and a tetragonal crystal (hereinafter sometimes referred to as a T phase) and an X-ray diffraction intensity ratio of specific faces of a tetragonal crystal and a cubic crystal (hereinafter sometimes referred to as a C phase) within a specific range.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 56-042909 Summary of the invention

[0008] In recent years, in the automotive field, idle stop and hybrid technology are necessary to meet environmental regulations and reduce fuel consumption. As a result, the number of times the engine is switched on and off has increased significantly, and water is easily retained in the exhaust pipe. There is a tendency for the amount of water covering the gas sensor installed in the exhaust pipe to increase. Therefore, the gas sensor is easily exposed to the hot and cold cycle caused by the high heat caused by the exhaust gas and the cooling caused by the water covering. Therefore, the solid electrolyte used in the gas sensor is required to ensure strength even after the hot and cold cycle. However, the solid electrolyte used in the previous gas sensor has an unstable phase that undergoes phase change in the temperature range of 100°C to 300°C. The stress caused by the volume change accompanying the phase change causes the crack to expand and the strength to decrease.

[0009] In the above-mentioned prior art, based on the crystallographic expectation, the tetragonal crystal (T phase) that is easy to phase change is regarded as an unstable phase, and the monoclinic phase (M phase) and cubic crystal (C phase) other than it are regarded as stable phases. It is envisaged that the strength of the ZrO2-Y2O3 solid electrolyte system can be improved by reducing the ratio of the amount of the T phase relative to the total amount of the crystal evaluated by X-ray diffraction. However, the above-mentioned prior art only evaluates the strength based on the initial crystal state. Since even the same T phase has a phase that undergoes a crystal phase change and a phase that does not undergo a crystal phase change, it is difficult to suppress the strength reduction caused by the cold and hot cycle by simply reducing the T phase without considering this point.

[0010] An object of the present disclosure is to provide a gas sensor having a solid electrolyte capable of suppressing a decrease in strength due to thermal cycling, and to provide a gas sensor powder suitable for producing the solid electrolyte in the gas sensor.

[0011] One embodiment of the present disclosure relates to a gas sensor having a solid electrolyte composed of zirconium oxide containing yttria, wherein:

[0012] In the solid electrolyte,

[0013] The mol% of Y2O3 relative to the total of ZrO2 and Y2O3 in the entire cross section of the solid electrolyte is 3.5 mol% or more and 6.9 mol% or less,

[0014] In the cross-section of the solid electrolyte, when the area ratio of the region where the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 is less than 3.3 mol% relative to the entire cross-section is set to A%, and the area ratio of the region where the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 is greater than 7 mol% relative to the entire cross-section is set to B%, the total of A and B, that is, the total area ratio (A+B), is greater than 10%.

[0015] Another aspect of the present disclosure relates to a gas sensor powder having granulated particles including a plurality of zirconium oxide particles and a plurality of yttrium oxide particles, wherein:

[0016] In the granulated particles,

[0017] The mol% of Y2O3 relative to the total of ZrO2 and Y2O3 is 3.5 mol% or more and 6.9 mol% or less,

[0018] having aggregated particles formed by agglomerating the yttrium oxide particles,

[0019] The aggregated particles have an aggregated particle size of 1 μm or more.

[0020] The gas sensor has the above-mentioned configuration. Therefore, according to the gas sensor, it is possible to suppress a decrease in the strength of the solid electrolyte due to a thermal cycle.

[0021] The gas sensor powder has the above-mentioned configuration. Therefore, according to the gas sensor powder, a solid electrolyte can be produced that can suppress a decrease in strength due to thermal cycling.

[0022] It should be noted that the symbols in parentheses in the claims indicate the correspondence with the specific means described in the embodiments described later, and do not limit the technical scope of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The above-mentioned purpose and other purposes, features and advantages of the present disclosure will become more apparent through the following detailed description with reference to the accompanying drawings. The accompanying drawings are as follows:

[0024] Figure 1 It is a cross-sectional view of the gas sensor (cup type) according to the first embodiment.

[0025] Figure 2 It is a magnified representation Figure 1 A cross-sectional view of a portion of a gas sensor element included in a gas sensor.

[0026] Figure 3 This is a cross-sectional view schematically showing the microstructure of the solid electrolyte of the gas sensor according to the first embodiment.

[0027] Figure 4 This is a cross-sectional view schematically showing a microstructure of a solid electrolyte in a comparative embodiment compared with the microstructure of the solid electrolyte of the gas sensor according to the first embodiment.

[0028] Figure 5 It is a cross-sectional view of the gas sensor (laminated type) according to the first embodiment.

[0029] Figure 6 It is a magnified representation Figure 5 A cross-sectional view of a gas sensor element included in a gas sensor.

[0030] Figure 7 This is an explanatory diagram schematically showing granulated particles of the gas sensor powder according to the second embodiment.

[0031] Figure 8 It is an explanatory diagram showing a method for producing gas sensor powder according to the third embodiment.

[0032] Fig. 9 It is an explanatory diagram of a measurement sample of a solid electrolyte provided for SEM-EDX analysis.

[0033] Fig.10 This is a diagram showing an example of a quantitative mapping image of the Y element expressed in atom % obtained by SEM-EDX analysis of a solid electrolyte.

[0034] Fig.11 It is used for Fig.10 The figure illustrates the image processing of the quantitative image of the Y element based on ImageJ. (a) Fig.10 (b) is an image in which the black area where the Y / (Zr+Y) atom % is less than 6.7 atom % is extracted in red, and (a) is an image showing the setting screen of the threshold selection tool of ImageJ when the image of (a) is obtained.

[0035] Fig.12 It is used for Fig.10 The figure illustrates the image processing of the quantitative image of the Y element based on ImageJ. (a) Fig.10 (b) is an image in which white areas where the Y / (Zr+Y) atom % is 13.4 atom % or more are extracted in red, and (a) is an image showing the setting screen of the threshold selection tool of ImageJ when the image of (a) is obtained.

[0036] Fig.13 This is a diagram showing an example of a quantitative mapping image of the Y element expressed in atom % obtained by SEM-EDX analysis of granulated particles included in the gas sensor powder.

[0037] Fig.14 It means that it will be reflected in Fig.13 FIG. 1 is a diagram showing a state in which the periphery of a granulated particle in a quantitative image of the Y element is surrounded by a line.

[0038] Fig.15 About Fig.14 The quantitative image of the Y element in which the central granulated particles among the plurality of granulated particles contained are filled and corrected by coloring the aggregated particles having an aggregated particle size of less than 1 μm in black.

[0039] Fig.16 It is a diagram for explaining the aggregated particle size of aggregated particles.

[0040] Fig.17 It is used for Fig.15 The figure illustrates the image processing of the quantitative image of the Y element based on ImageJ. (a) Fig.15 (b) is an image in which white areas where Y / (Zr+Y) atom % is 20 atom % or more are extracted in red, and (a) is an image showing the setting screen of the threshold selection tool of ImageJ when the image of (a) is obtained.

[0041] Fig.18 This is a diagram for explaining a measurement method for measuring the water coverage strength of a solid electrolyte in Experimental Example 1.

[0042] Fig.19 This is a graph showing the relationship between Y2O3 / (ZrO2+Y2O3) mol% [mol%] in the entire cross section of the solid electrolyte obtained in Experimental Example 1 and the water coverage strength [μL] of the solid electrolyte.

[0043] Fig. 20 This is a graph showing the relationship between the total area ratio (A+B) [%] in the cross section of the solid electrolyte obtained in Experimental Example 3 and the strength [MPa] of the solid electrolyte after thermal cycling.

[0044] Fig.21 This is a graph showing the relationship between the area ratio C [%] of aggregated particles having an aggregate particle size of 1 μm or more to the cross-sectional area of ​​granulated particles obtained in Experimental Example 4 and the total area ratio (A+B) [%] in the solid electrolyte.

[0045] Fig. 22 This is a graph showing the relationship between the pH value in the slurry pH adjustment step and the area ratio C [%] of aggregated particles having an aggregate particle size of 1 μm or more to the cross-sectional area of ​​granulated particles obtained in Experimental Example 5. DETAILED DESCRIPTION

[0046] (Implementation Method 1)

[0047] Reference Figure 1 to Figure 6 The gas sensor of Embodiment 1 is described. Figure 1 to Figure 6 As shown in the example, the gas sensor 1 of the present embodiment is a gas sensor having a solid electrolyte 21 composed of zirconium oxide containing yttria. In the gas sensor 1 of the present embodiment, the solid electrolyte 21 is as follows. Figure 3 As shown in FIG. 1 , the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 in the entire cross section of the solid electrolyte 21 is 3.5 mol% or more and 6.9 mol% or less. Figure 3 As shown, in the cross section of the solid electrolyte 21, when the area ratio of region 211 in which the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 is less than 3.3 mol% relative to the entire cross section is set to A[%], and the area ratio of region 212 in which the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 is greater than 7 mol% relative to the entire cross section is set to B[%], the total of A and B, that is, the total area ratio (A+B), is greater than 10%.

[0048] The mol% of Y2O3 relative to the total of ZrO2 and Y2O3 in the entire cross section of the solid electrolyte 21 (hereinafter sometimes referred to as premise Y2O3 / (ZrO2+Y2O3)mol%) means the amount of Y2O3 contained in the entire solid electrolyte 21 as a premise (the amount of Y2O3 doped in the solid electrolyte 21). The premise Y2O3 / (ZrO2+Y2O3)mol% is an indicator related to the water coverage strength (μL) of the solid electrolyte 21 when covered with water during heating use of the gas sensor 1. If the premise Y2O3 / (ZrO2+Y2O3)mol% is less than 3.5mol% or greater than 6.9mol%, the water coverage strength decreases. It is believed that this is because the difference in thermal expansion coefficient between the solid electrolyte 21 and the electrode increases, which causes stress relative to the temperature drop when covered with water, resulting in peeling of the electrode, etc. In contrast, when the Y2O3 / (ZrO2+Y2O3) mol% is set to 3.5 mol% or more and 6.9 mol% or less, a higher water coverage strength can be obtained. This is considered to be because the difference in thermal expansion coefficients between the solid electrolyte 21 and the electrode is relatively small, so that stress is less likely to be generated due to the temperature drop during water coverage, and it is less likely to cause peeling of the electrode. In addition, in this case, the oxygen ion conductivity also becomes suitable for the gas sensor 1.

[0049] like Figure 3As shown, in the cross section of the solid electrolyte 21, a region 211 in which the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 (hereinafter sometimes referred to as Y2O3 / (ZrO2+Y2O3) mol%) is less than 3.3 mol% has the significance of being a stable region that is difficult to undergo phase change due to thermal cycling. This region 211 is referred to as the first stable region 211. Specifically, at the operating temperature of the gas sensor 1 (e.g., room temperature to 950°C), in the first stable region 211, the M phase is in a stable state, and even if subjected to thermal cycling, the M phase is difficult to undergo phase change. In addition, in the cross section of the solid electrolyte 21, a region 212 in which the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 is more than 7 mol% has the significance of being a stable region that is difficult to undergo phase change due to thermal cycling. This region 212 is referred to as the second stable region 212. Specifically, in the second stable region 212, since the M phase is not in a quasi-stable state, the C phase and the T phase become the main body. The C phase and the T phase do not transform into the M phase even if subjected to a cold and hot cycle, so they are stable. That is, the first stable region 211 and the second stable region 212 (hereinafter, these are sometimes collectively referred to as stable regions 211 and 212) can also be said to be regions where the probability of phase transformation is low even if subjected to a cold and hot cycle. In contrast, in the cross section of the solid electrolyte 21, the region 213 where the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 is 3.4 mol% or more and 6.9 mol% or less is an unstable region that is prone to phase transformation due to a cold and hot cycle. In this unstable region 213, the crystalline phase transforms into a variety of crystalline forms due to a cold and hot cycle in the temperature range of 0°C to 1000°C.

[0050] In the first stable region 211, from the viewpoint of ensuring oxygen ion conductivity, etc., it is preferred that Y2O3 / (ZrO2+Y2O3)mol% is greater than 0mol%. In addition, in the second stable region 212, from the viewpoint of suppressing leakage current caused by crystal defects, etc., it is preferred that Y2O3 / (ZrO2+Y2O3)mol% is less than 20mol%.

[0051] Here, in the cross section of the solid electrolyte 21, the total of the area ratio A[%] of the first stable region 211 where Y2O3 / (ZrO2+Y2O3)mol% is less than 3.3mol% relative to the entire cross section and the area ratio B[%] of the second stable region 212 where Y2O3 / (ZrO2+Y2O3)mol% is greater than 7mol% relative to the entire cross section, that is, the total area ratio (A+B)[%] can be set to be greater than 10%. If the total area ratio (A+B) in the solid electrolyte 21 is less than 10%, the strength of the solid electrolyte 21 after thermal cycling decreases. This is considered to be because, when the total area ratio (A+B) in the solid electrolyte 21 is less than 10%, as Figure 4 As shown in the figure, the unstable region 213 is more than 90%, so when the solid electrolyte 21 is exposed to the cold and hot cycle in the exhaust pipe, the crystal phase changes into a variety of crystal forms. Figure 4 The inter-particle bonding in the solid electrolyte 21 is broken, and the strength is reduced. Figure 3 As shown in FIG. 1 , as long as the total area ratio (A+B) in the solid electrolyte 21 is 10% or more, the strength after the thermal cycle can be improved compared to when the total area ratio (A+B) is less than 10%. This is considered to be because the ratio of the unstable region 213 is reduced, the ratio of the stable regions 211 and 212 is increased, and the stress ( Figure 3 The arrow in the figure) decreases, the fracture of the inter-particle bond slows down, and the strength loss can be suppressed.

[0052] The total area ratio (A+B) in the solid electrolyte 21 is preferably greater than 20% and less than 98%. According to this structure, since the strength is sufficiently increased compared to the stress formed by the phase change according to the ratio of the unstable region 213 and the stable regions 211 and 212, the strength is more difficult to decrease. Therefore, this structure is suitable for a cup-shaped gas sensor 1 that requires particularly high strength after cold and hot cycles. Of course, this structure is applicable not only to cup-shaped gas sensors 1 but also to stacked gas sensors 1. Furthermore, if the total area ratio (A+B) in the solid electrolyte 21 is less than 20% or greater than 98%, although the strength after cold and hot cycles can be sufficiently improved compared to when the total area ratio (A+B) is less than 10%, there is a tendency for the strength after cold and hot cycles to decrease somewhat compared to when the total area ratio (A+B) is greater than 20% and less than 98%. When the total area ratio (A+B) exceeds 98%, the strength after the cold and hot cycle decreases. It is believed that although the stress caused by phase change is reduced, the application of thermal expansion stress increases due to the reduction of the buffer phase in the thermal expansion surface, which reduces the strength of the solid electrolyte 21. The gas sensor 1 in which the total area ratio (A+B) in the solid electrolyte 21 is 10% or more and less than 20%, or exceeds 98%, can be suitable as a stacked gas sensor 1 that can use a solid electrolyte 21 with lower strength than the cup-type gas sensor 1. Of course, this structure is applicable not only to the stacked gas sensor 1 but also to the cup-type gas sensor 1.

[0053] Thus, the gas sensor 1 of the present embodiment is based on the knowledge that the boundary between the stable phase and the unstable phase in the solid electrolyte 21 at the operating temperature of the gas sensor 1 is defined by the Y2O3 / (ZrO2+Y2O3)mol% in the crystal phase. In addition, the gas sensor 1 of the present embodiment makes it difficult to generate an unstable phase by coordinating the segregation of Y2O3 in the solid electrolyte 21 in such a manner as to achieve the above-mentioned definition. In addition, in the gas sensor 1 of the present embodiment, the above-mentioned definition is formed not only in view of the prediction of crystallography, but also in view of the change in the probability of the crystal phase transition by Y2O3 / (ZrO2+Y2O3)mol% when subjected to a thermal cycle. As described above, according to the gas sensor 1 of the present embodiment, it is possible to suppress the decrease in the strength of the solid electrolyte 21 caused by the thermal cycle.

[0054] In the cross section of the solid electrolyte 21, the above-mentioned area ratio A[%] is preferably greater than 0%. According to this structure, it is easy to obtain a solid electrolyte 21 in which Y2O3 is segregated in the manner specified above, and it is also easy to match the thermal expansion coefficient between the solid electrolyte 21 and the electrode. In addition, in the cross section of the solid electrolyte 21, a structure in which the area ratio B[%] is greater than the area ratio A[%] can be formed. According to this structure, the strength reduction of the solid electrolyte 21 caused by the cold and hot cycle can be reliably suppressed.

[0055] Furthermore, the premise Y2O3 / (ZrO2+Y2O3)mol% in the solid electrolyte 21 can be measured by SEM-EDX analysis. In addition, in the cross section of the solid electrolyte 21, the area ratio A[%] of the region 211 where Y2O3 / (ZrO2+Y2O3)mol% is less than 3.3mol% relative to the entire cross section, and the area ratio B[%] of the region 212 where Y2O3 / (ZrO2+Y2O3)mol% is more than 7mol% relative to the entire cross section can be measured by SEM-EDX analysis and image processing. These measurement methods will be described later through experimental examples. In addition, an example of a method for manufacturing the solid electrolyte 21 in the gas sensor 1 of this embodiment will be described later through embodiments 2 and 3.

[0056] In the present embodiment, the structure of the gas sensor 1 having the above-mentioned solid electrolyte 21 is not particularly limited. Specifically, the gas sensor 1 can be configured to include: a gas sensor element 2 including a solid electrolyte 21, a housing 3 in which the gas sensor element 2 is inserted and held, a cover 4 for protecting the front end of the gas sensor element 2, and a heater 5 for heating the gas sensor element 2.

[0057] The gas sensor 1 can be used, for example, Figure 1The cup-shaped gas sensor 1 is constructed as shown in the example. In this case, the gas sensor element 2 is as shown in FIG. Figure 1 and Figure 2 As shown in the example, it can include: a solid electrolyte 21 formed in a bottomed cylindrical shape with one end closed and the other end open (so-called cup-shaped); a standard electrode 22 provided on the inner surface of the solid electrolyte 21 for contacting with a standard gas such as the atmosphere; and a measuring electrode 23 provided on the outer surface of the solid electrolyte 21 for contacting with the exhaust gas to be measured.

[0058] Figure 2 In the embodiment, the surface of the measuring electrode 23 may be covered with one or more protective layers 24 . Figure 2 , the surface of the measuring electrode 23 is covered with a first protective layer 241, the surface of the first protective layer 241 is covered with a second protective layer 242, and the surface of the second protective layer 242 is covered with a third protective layer 243. The protective layer 24 is used to protect the measuring electrode 23 from sulfur (S), phosphorus (P), glassy toxic substances, etc. contained in the exhaust gas, or to adjust the amount of gas reaching the measuring electrode 23, and can be composed of porous materials. The material, porosity, thickness, etc. of each protective layer 24 can be appropriately changed according to the purpose.

[0059] In addition, the gas sensor 1 can also be used, for example Figure 5 In this case, the gas sensor element 2 is constituted as a stacked type gas sensor 1 as shown in the example. Figure 6 As shown in the example, it comprises: a layered solid electrolyte 21; a standard electrode 22 provided on one surface of the solid electrolyte 21 for contacting a standard gas such as the atmosphere; and a measuring electrode 23 provided on the other surface of the solid electrolyte 21 for contacting an exhaust gas to be measured.

[0060] Figure 6 In the figure, at the front end of the gas sensor element 2, an exhaust gas inlet portion (not shown) is formed for introducing exhaust gas into the interior. On one surface of the solid electrolyte 21, a standard gas space 220 for circulating the standard gas is provided, and a standard electrode 22 is arranged on the side of the standard gas space 220. On the other surface of the solid electrolyte 21, an exhaust gas space 230 for circulating the exhaust gas is provided, and a measuring electrode 23 is arranged on the side of the exhaust gas space 230. The other surface side of the solid electrolyte 21 is maintained by an insulating retaining layer 25. In the retaining layer 25, a heater 5 for heating the gas sensor element 2 is provided. On the outer peripheral surface of the gas sensor element 2, a protective layer 24 is formed to protect the gas sensor element 2 from poisoning and water coverage. Furthermore, with respect to other structures in the gas sensor 1, known technologies can be appropriately adopted.

[0061] (Implementation Method 2)

[0062] Reference Figure 7 The gas sensor powder according to Embodiment 2 is described below. Note that, in Embodiment 2 and thereafter, the same reference numerals as those used in the previous embodiments represent the same constituent elements as those in the previous embodiments unless otherwise indicated.

[0063] like Figure 7 As illustrated, the gas sensor powder 6 of the present embodiment has granulated particles 60 including a plurality of zirconium oxide particles 61 and a plurality of yttrium oxide particles 62. In the granulated particles 60, the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 is 3.5 mol% or more and 6.9 mol% or less. The granulated particles 60 have agglomerated particles 620 agglomerated from the yttrium oxide particles 62. The agglomerated particle size of the agglomerated particles 620 is 1 μm or more.

[0064] The zirconium oxide particles 61 and the yttrium oxide particles 62 in the granulated particles 60 are as follows: Figure 7 As shown in the examples, they are all primary particles. Figure 7 6 shows an example in which the granulated particles 60 are composed of a plurality of zirconium oxide particles 61 and a plurality of yttrium oxide particles 62. The mol% of Y2O3 relative to the total of ZrO2 and Y2O3 in the granulated particles 60 (hereinafter, sometimes referred to as added Y2O3 / (ZrO2+Y2O3)mol%) means the amount of Y2O3 contained in the granulated particles (the amount of Y2O3 added to the granulated particles). Added Y2O3 / (ZrO2+Y2O3)mol% is an indicator related to the amount of Y2O3 contained in the entire solid electrolyte 21 formed (the amount of Y2O3 doped in the solid electrolyte), that is, the premise Y2O3 / (ZrO2+Y2O3)mol% of the solid electrolyte 21 formed. If the added Y2O3 / (ZrO2+Y2O3)mol% is lower than 3.5mol% or higher than 6.9mol%, the solid electrolyte 21 of embodiment 1 cannot be produced because the premise of the solid electrolyte 21, Y2O3 / (ZrO2+Y2O3)mol%, is out of range.

[0065] The granulated particles 60 have aggregated particles 620 formed by agglomerating yttrium oxide particles 62. Specifically, the aggregated particles 620 are granular portions in which the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 is 10 mol% or more. Figure 7 As illustrated, a plurality of aggregated particles 620 exist on the surface of the zirconium oxide particle 61 . Figure 7 , an example is shown in which yttrium oxide particles 62 having a smaller particle size than the particle size of zirconium oxide particles 61 are present on the surface of zirconium oxide particles 61. Figure 7As illustrated, the granulated particles 60 may contain unagglomerated yttrium oxide particles 62. Specifically, the gas sensor powder 6 may be composed of an aggregate of the granulated particles 60.

[0066] Here, the granulated particles 60 have agglomerated particles 620 with a particle size of 1 μm or more. In the absence of agglomerated particles 620 with a particle size of 1 μm or more, when the solid electrolyte 21 is manufactured, the total area ratio (A+B) in the solid electrolyte 21 cannot be set to 10% or more. This is considered to be because, in the above case, the yttrium oxide particles 62 in the granulated particles 60 are uniformly dispersed, and the yttrium oxide is also uniformly dissolved in the zirconium oxide during firing. As a result, it is difficult to produce segregation of yttrium oxide, and it is easy to produce an unstable phase. In contrast, in the case of agglomerated particles 620 with a particle size of 1 μm or more, when the solid electrolyte 21 is manufactured, the total area ratio (A+B) in the solid electrolyte 21 can be set to 10% or more. This is considered to be because, as Figure 7 As shown in the example, the yttrium oxide particles 62 are unevenly present in the granulated particles 60, and the yttrium oxide is also unevenly present during firing, resulting in the segregation of yttrium oxide and difficulty in generating an unstable phase. In addition, as long as the granulated particles 60 contain the agglomerated particles 620 with an agglomerated particle size of 1 μm or more, they may also contain the agglomerated particles 620 with an agglomerated particle size of less than 1 μm.

[0067] According to the gas sensor powder 6 of the present embodiment, by appropriately adding a binder or the like to the gas sensor powder 6 as needed, after forming a molded body by molding, the obtained molded body is fired, and the solid electrolyte 21 of the first embodiment can be produced. It is believed that this is because, according to the above-mentioned structure, yttrium oxide can be segregated in the state of a molded body, and thus, a solid electrolyte 21 in which yttrium oxide is segregated can be produced by firing it. Furthermore, regarding the molding method, firing conditions, etc. of the molded body, the molding method and firing conditions known in the past can be adopted. Therefore, according to the gas sensor powder 6 of the present embodiment, a solid electrolyte 21 that can suppress the decrease in strength caused by cold and hot cycles can be produced.

[0068] In the cross section of the granulated particle 60, the area ratio C[%] of the agglomerated particles 620 having an agglomerated particle diameter of 1 μm or more relative to the cross-sectional area of ​​the granulated particle 60 can be set to be 0.5% or more and 4% or less. According to this configuration, when the solid electrolyte 21 is produced, the total area ratio (A+B) in the solid electrolyte 21 can be set to be 20% or more and 98% or less. Therefore, according to this configuration, as described in Embodiment 1, by reducing the unstable region 213, the solid electrolyte 21 having an excellent effect of suppressing the decrease in strength can be produced. If the area ratio C[%] exceeds 4%, the segregation of the yttrium oxide particles 62 in the granulated particle 60 is excessive, so that the total area ratio (A+B) in the solid electrolyte 21 exceeds 98%, and there is a tendency for the strength after the cold and hot cycle to decrease to some extent.

[0069] The average particle size of the granulated particles 60 can be set to, for example, 20 μm or more and 100 μm or less. According to this structure, there are advantages such as high fluidity when filling into the mold and difficulty in generating defects in the solid electrolyte 21. Furthermore, the average particle size of the granulated particles 60 is the average value of the maximum outer diameter values ​​of 10 granulated particles 60 measured by SEM observation. In addition, it is preferred that the granulated particles 60 have a plurality of agglomerated particles 620 having a coagulated particle size of 2 μm or more and 15 μm or less. According to this structure, the above-mentioned solid electrolyte 21 can be reliably produced. In addition, there are advantages such as further improvement of oxygen ion conductivity.

[0070] Furthermore, the added Y2O3 / (ZrO2+Y2O3) mol% in the granulated particles 60 can be measured by SEM-EDX analysis. In addition, the agglomerated particle size of the agglomerated particles 620 and the area ratio C of the agglomerated particles 620 with an agglomerated particle size of 1 μm or more relative to the cross-sectional area of ​​the granulated particles 60 can be measured by SEM-EDX analysis and image processing. These measurement methods will be described later through experimental examples. In addition, an example of a method for manufacturing the gas sensor powder 6 of this embodiment will be described later through Embodiment 3.

[0071] (Implementation 3)

[0072] Reference Figure 8 The method for producing the gas sensor powder according to the third embodiment will be described. The method for producing the gas sensor powder according to the present embodiment (hereinafter sometimes referred to as "the present production method") is a production method capable of producing the gas sensor powder 6 according to the second embodiment. Figure 8 As shown, the present production method includes a slurry preparation step 71 , a slurry pH adjustment step 72 , a slurry shaking step 73 , and a powderization step 74 .

[0073] The slurry preparation step 71 is a step of preparing an acidic slurry by mixing Y2O3 powder and ZrO2 powder, a solvent and an acid in a manner such that the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 reaches 3.5 mol% or more and 6.9 mol% or less, and adjusting the pH thereof to 3 or more and 4 or less.

[0074] The average particle size of Y2O3 powder can be selected from the range of 0.01 to 10 μm, and the average particle size of ZrO2 powder can be selected from the range of 0.5 to 30 μm. The above average particle size is the particle size (diameter) d50 when the cumulative frequency distribution of the volume standard measured by the laser diffraction scattering method represents 50%. As a solvent, for example, polar solvents such as water, ethanol, methanol, and ethylene glycol can be exemplified. As an acid, for example, halogen-free acids such as acetic acid, formic acid, and nitric acid can be exemplified.

[0075] The slurry pH adjustment step 72 is a step of adding an alkaline solution to the slurry to adjust the pH of the slurry to an alkaline level of 10 or more and 12 or less.

[0076] As the alkaline solution, for example, an aqueous solution containing at least one of an alkali metal and an alkaline earth metal, an alkaline aqueous solution not containing both an alkali metal and an alkaline earth metal, etc. can be exemplified. As the former aqueous solution, a NaOH aqueous solution can be cited, and as the latter aqueous solution, an ammonia aqueous solution can be cited. Preferably, an alkaline aqueous solution not containing both an alkali metal and an alkaline earth metal, such as an ammonia aqueous solution, is cited. This is because alkali metals and alkaline earth metals are unlikely to have an adverse effect on the sensing performance of the gas sensor.

[0077] If the pH of the slurry is adjusted to an alkalinity of 10 or more and 12 or less, the zeta potential of Y2O3 approaches 0 mV. As a result, the zirconium oxide particles do not aggregate, but the yttrium oxide particles easily aggregate. Therefore, by adjusting the pH of the slurry to an alkalinity of 10 or more and 12 or less in advance, the yttrium oxide particles can be aggregated by moving and colliding with each other in the subsequent slurry shaking step 73.

[0078] The slurry shaking step 73 is a step of shaking the slurry whose pH is adjusted to alkaline, thereby causing yttrium oxide particles in the slurry to move and collide with each other and aggregate.

[0079] The powdering step 74 is a step of drying and granulating the slurry to obtain the gas sensor powder 6 having granulated particles 60 including a plurality of zirconium oxide particles 61 and a plurality of yttrium oxide particles 62 .

[0080] The drying and granulation of the slurry can be carried out by, for example, a spray dryer or the like.

[0081] Furthermore, the solid electrolyte 21 of the gas sensor 1 can be manufactured by a molding step of molding the gas sensor powder 6 obtained as described above to form a molded body, and a firing step of firing the formed molded body. Examples of the firing conditions include a firing temperature of 1200° C. to 1500° C. and a firing time of 0.5 hours to 24 hours.

[0082] (Experimental example)

[0083] <Various measurement methods>

[0084] (1) Method for measuring the area ratio A [%] of the first stable region, the area ratio B [%] of the second stable region, and the total area ratio (A+B) [%] in the cross section of the solid electrolyte

[0085] like Fig. 9 As shown in FIG. 1 , the solid electrolyte 21 is ground so that the cross section along the length direction of the solid electrolyte 21 includes the central axis of the solid electrolyte 21, and a measurement sample S is prepared. Using the EDX of the SEM-EDX analysis device, element information data of the surface area on the exhaust side of the measurement sample S is obtained. At this time, as for the SEM-EDX device, the S8000 manufactured by Hitachi High-Technologies Corporation, which is an EDX device with a FlatQuad manufactured by Bruker, is used. At this time, the measurement conditions of the SEM are set to an acceleration voltage of 15 kV, a current of 15 μA, and a measurement magnification of 10,000 times (10k). In addition, the surface area for obtaining element information data includes the surface 210 facing the exhaust, and the size is set to a length of 12 μm in the length direction of the solid electrolyte 21 and a length of 9 μm in the thickness direction of the solid electrolyte 21. The above element information data is obtained by using the super imaging function of the above EDX device under the measurement conditions of filter: sharp cutoff, resolution: 1 / 4, and measurement time: 600 s.

[0086] The obtained element information data was processed using the quantitative imaging function of the above-mentioned EDX device. At this time, only the selected elements were quantified as Y (yttrium) element and Zr (zirconium) element. Next, only the Y element was selected as the representative element of the quantitative imaging image, and then the data processing software in the above-mentioned EDX device was set in a manner expressed in atom%. Here, the conversion from the atom% of Y relative to the total of Zr and Y (hereinafter sometimes referred to as Y / (Zr+Y)atom%) to the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 (Y2O3 / (ZrO2+Y2O3)mol%) can be implemented according to the following formula 1.

[0087] When Y / (Zr+Y)atom% is set to A,

[0088] A / {A+2×(100-A)} Formula 1

[0089] If Y / (Zr+Y)atom% corresponding to Y2O3 / (ZrO2+Y2O3)mol% of 3.3mol% is calculated from the above formula 1, it is 6.7atom%. Similarly, if Y / (Zr+Y)atom% corresponding to Y2O3 / (ZrO2+Y2O3)mol% of 7mol% is calculated, it is 13.4atom%. Therefore, the color palette of the data processing software in the above EDX device is adjusted in such a way that the area with Y / (Zr+Y)atom% below 6.7atom% is black and the area with Y / (Zr+Y)atom% above 13.4atom% is white, and for solid electrolyte 21, the following is obtained: Fig.10 A quantitative map image of the Y element expressed in atom % as shown (hereinafter sometimes referred to as a Y map image).

[0090] Next, in order to calculate the area ratio A[%] of the region where Y2O3 / (ZrO2+Y2O3)mol% is less than 3.3mol% in the cross section of the solid electrolyte 21 of the measurement sample S relative to the entire cross section, the Y image obtained as described above was processed. ImageJ compiled by the National Institutes of Health (NIH) of the United States was used as image processing software. The version of ImageJ is 1.52a. Specifically, the image style was changed to 8-bit using the image tool of ImageJ. Next, as Fig.11 As shown in (a) and (b), the extraction area was set in red using the threshold selection tool of ImageJ, and the threshold was set so that the black area with Y / (Zr+Y)atom% of 6.7atom% or less could be extracted. Fig.11 The color of the extracted area 91 in (a) is actually red. Next, the area selection tool of ImageJ was used to select a range of 12 μm in width and 9 μm in length. Next, Areafraction was checked through ImageJ's Analyze→Measurement→Result→Set Measurement. Then, since the value Area% appears in the Result column of ImageJ, the area ratio A1[%] of the area where Y2O3 / (ZrO2+Y2O3)mol% is less than 3.3mol% in the cross section of the solid electrolyte 21 of the measured sample S relative to the entire cross section is recorded.

[0091] Next, in order to calculate the area ratio B [%] of the region where Y2O3 / (ZrO2+Y2O3) mol% is 7 mol% or more in the cross section of the solid electrolyte 21 of the measurement sample S, the Y image obtained as described above was subjected to image processing in the same manner as described above. Fig.12 As shown in (a) and (b), the extraction area was set in red using the threshold selection tool of ImageJ, and the threshold was set so that the white area with Y / (Zr+Y)atom% of 13.4atom% or more could be extracted. Fig.12 The color of the extracted area 92 in (a) is actually red. Next, using the area selection tool of ImageJ, a range of 12μm in width and 9μm in height was selected. Next, the Area fraction was checked through ImageJ's Analyze→Measurement→Result→Set Measurement. Then, since the value Area% appears in the Result column of ImageJ, the area ratio B1[%] of the area where the Y2O3 / (ZrO2+Y2O3)mol% in the cross section of the solid electrolyte 21 of the measured sample S is 7mol% or more relative to the entire cross section is recorded.

[0092] Next, by adding the area ratio A1[%] and the area ratio B1[%] obtained as described above, the total area ratio (A1+B1)[%] was calculated. By respectively performing the above steps on the element information data obtained from the five surface areas on the exhaust side of the measurement sample S, the area ratios A1[%] to A5[%], the area ratios B1[%] to B5[%], and the total area ratios (A1+B1)[%] to (A5+B5)[%] were calculated. Furthermore, the five surface areas on the exhaust side of the measurement sample S were measured as follows: Fig. 9 As shown, the intervals between the surface areas are set to a minimum of 1 mm or more. Then, the arithmetic mean of the five total area ratios (A1+B1)[%] to (A5+B5)[%] obtained is taken as the total area ratio (A+B)[%] in the cross section of the solid electrolyte 21.

[0093] (2) Method for determining Y2O3 / (ZrO2+Y2O3) mol% in the entire cross section of a solid electrolyte

[0094] Similar to the above-mentioned <(1) Method for determining the area ratio A[%] of the first stable region, the area ratio B[%] of the second stable region, and the total area ratio (A+B)[%] in the cross section of the solid electrolyte>, the element information data obtained from the surface area on the exhaust side of the measurement sample S was processed using the surface analysis function of the data processing software of the above-mentioned EDX device, which can calculate the average value of the entire selected area. At this time, the entire field of view of the measurement site, i.e., the surface area, was selected, and the selected elements were quantified as only the Y element and the Zr element. Then, the Y / (Zr+Y)atom% contained in the entire surface area of ​​the measurement site was calculated, and by converting it according to the above-mentioned formula 1, the Y2O3 / (ZrO2+Y2O3)mol% contained in the entire surface area of ​​the measurement site was calculated.

[0095] Through from Fig. 9 The above steps were respectively applied to the element information data obtained from the five surface regions on the exhaust side of the measurement sample S shown, and the Y2O3 / (ZrO2+Y2O3)mol% contained in the entire surface region was calculated. Then, the arithmetic mean of the Y2O3 / (ZrO2+Y2O3)mol% contained in the entire five surface regions was taken as the Y2O3 / (ZrO2+Y2O3)mol% in the entire cross section of the solid electrolyte.

[0096] (3) Method for measuring the area ratio C [%] of aggregated particles having an aggregate particle size of 1 μm or more in the cross section of granulated particles of gas sensor powder relative to the cross-sectional area of ​​the granulated particles

[0097] After the granulated particles are embedded in the resin, a cross section is ground out by grinding in a manner that passes through the center of the granulated particles to prepare a measurement sample. The element information data of the cross section of the measurement sample is obtained by using the EDX of the SEM-EDX analysis device. At this time, the SEM-EDX device is an S8000 manufactured by Hitachi High-Technologies Corporation, which is an EDX device with a FlatQuad manufactured by Bruker. At this time, the measurement conditions of the SEM are set to an acceleration voltage of 15 kV, a current of 15 μA, and a measurement magnification of 1100 times (1.1 k). In addition, the above-mentioned element information data is obtained by using the hyper-imaging function of the above-mentioned EDX device under the measurement conditions of filter: sharp cutoff, resolution: 1 / 4, and measurement time: 600 s.

[0098] The obtained element information data was processed using the quantitative imaging function of the above-mentioned EDX device. At this time, only the selected elements were quantified as Y (yttrium) element and Zr (zirconium) element. Next, only the Y element was selected as the representative element of the quantitative imaging image, and the data processing software in the above-mentioned EDX device was set in a manner expressed in atom%. Next, if the above-mentioned formula 1 is used to calculate the Y / (Zr+Y)atom% equivalent to Y2O3 / (ZrO2+Y2O3)mol% of 10mol%, it is 20atom%. Therefore, the color palette of the data processing software in the above-mentioned EDX is adjusted in such a way that the area where Y / (Zr+Y)atom% is more than 20atom% appears white, and with regard to the granulated particles, the following is obtained. Fig.13 A quantitative map image (Y map image) of the Y element expressed in atom % as shown.

[0099] Next, in order to Fig.13 The Y image of the resin part is removed by mistake and compared with the SEM image. Fig.14 As shown in FIG. 1 , the outer periphery of the granulated particles is surrounded by a line. Fig.14 Among the plurality of granulated particles contained, the granulated particles whose outer shapes are within the field of view and which roughly represent the entire granulated particles are selected as the measurement object. Fig.14 Next, the selected granules are used to measure the agglomerated particles ( Fig.14 The agglomerated particle size is obtained by painting the agglomerated particles with an agglomerated particle size of less than 1 μm in black. Fig.15 The corrected Y image is shown in FIG. Fig.16 As shown in FIG. 1 , the aggregate particle size is the diameter of the smallest circle C that can make the aggregated particles 620 located inside in the Y image. When the granulated particles have an aggregate particle size of 1 μm or more, as shown in FIG. Fig.15 As shown in the image, white spots will definitely remain in the region of the granulated particles.

[0100] Next, in order to calculate the area ratio C[%] of the agglomerated particles with a particle size of 1 μm or more in the cross section of the granulated particles of the measured sample relative to the cross-sectional area of ​​the granulated particles, the corrected Y image obtained as described above was subjected to image processing. ImageJ compiled by the National Institutes of Health (NIH) of the United States was used as image processing software. The version of ImageJ is 1.52a. Specifically, the image style was changed to 8-bit using the image tool of ImageJ. Next, as Fig.17As shown in (a) and (b), the extraction area was set in red using the threshold selection tool of ImageJ, and the threshold was set so that the white area with Y / (Zr+Y)atom% of 20atom% or more could be extracted. Fig.17 The color of the extracted area 93 in (a) is actually red. Next, the shape of the granulated particles was selected using the area selection tool of ImageJ. Next, Area fraction was checked through Analyze→Measurement→Result→Set Measurement of ImageJ. In this way, since the value Area% appears in the Result column of ImageJ, the area ratio C1[%] of the agglomerated particles with an agglomerated particle size of 1 μm or more relative to the cross-sectional area of ​​the granulated particles in the cross section of the granulated particles of the measurement sample is recorded.

[0101] By performing the above steps on the element information data obtained from five different cross sections of the measured sample, the area ratios C1[%] to C5[%] were calculated. Then, the arithmetic mean of the five area ratios C1[%] to C5[%] obtained was used as the area ratio C[%] of the aggregated particles with an aggregated particle size of 1 μm or more in the cross section of the granulated particles relative to the cross-sectional area of ​​the granulated particles.

[0102] (4) Method for determining Y2O3 / (ZrO2+Y2O3) mol% in granulated particles of gas sensor powder

[0103] Similar to the above-mentioned <(3) Method for determining the area ratio [%] of agglomerated particles having an agglomerated particle size of 1 μm or more in the cross section of granulated particles of gas sensor powder>, the element information data obtained from the cross section of the measured sample is processed using the quantitative imaging function of the above-mentioned EDX device. At this time, the entire granulated particles to be measured are selected, and only the selected elements are quantified as Y element and Zr element. Then, the Y / (Zr+Y) atom% contained in the granulated particles in the entire field of view of the measured part excluding the resin part is calculated, and by converting it according to the above-mentioned formula 1, the Y2O3 / (ZrO2+Y2O3) mol% in the granulated particles is calculated.

[0104] <Experimental Example 1> - Relationship between Y2O3 / (ZrO2+Y2O3)mol% and water coverage strength in the entire cross section of a solid electrolyte -

[0105] Y2O3 powder and ZrO2 powder were mixed so that the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 was 3.5 mol% or more and 6.9 mol% or less, less than 3.5 mol% and more than 6.9 mol%, and water as a solvent and acetic acid as an acid were added to prepare a slurry. At this time, the pH of the slurry was set to 3 to 4. Furthermore, the average particle size of the Y2O3 powder was selected from the range of 0.01 to 10 μm, and the average particle size of the ZrO2 powder was selected from the range of 0.5 to 30 μm.

[0106] Next, ammonia water is added as an alkaline solution to the slurry whose pH is adjusted to 3 to 4, and the pH is adjusted to 10 to 12. Next, the slurry whose pH is adjusted to 10 to 12 is slowly shaken so that the yttrium oxide particles in the slurry are agglomerated by movement and collision. Next, the slurry is dried and granulated by a spray dryer. Thus, each gas sensor powder having granulated particles with different Y2O3 / (ZrO2+Y2O3)mol% is obtained. Furthermore, the gas sensor powder formed by mixing Y2O3 powder and ZrO2 powder in such a way that Y2O3 / (ZrO2+Y2O3)mol% reaches 3.5mol% or more and 6.9mol% or less has agglomerated particles formed by agglomeration of yttrium oxide particles, and the agglomerated particle size of the agglomerated particles is 1μm or more.

[0107] Next, each gas sensor powder is loaded into a mold and pressurized to obtain each molded body. Next, each molded body is sintered at 1350°C for 1 hour to obtain each solid electrolyte. Furthermore, in this example, each solid electrolyte is set to a cup-shaped cylindrical shape with a bottom. Next, for each obtained solid electrolyte, the Y2O3 / (ZrO2+Y2O3)mol% in the entire cross section of the solid electrolyte and the total area ratio (A+B) in the cross section of the solid electrolyte are measured by the above-mentioned measurement method. Furthermore, for a solid electrolyte in which the Y2O3 / (ZrO2+Y2O3)mol% in the entire cross section of the solid electrolyte is greater than 3.5mol% and less than 6.9mol%, the total area ratio (A+B) in the cross section of the solid electrolyte is greater than 10%.

[0108] Next, using each solid electrolyte, a Figure 2 The gas sensor element shown in FIG. 1 is a gas sensor element having a thickness of 100 μm. The first protective layer is made of aluminum magnesium spinel and has a thickness of 100 μm. The second protective layer is made of γ-alumina and has a thickness of 50 μm. The third protective layer is made of γ-alumina and has a thickness of 50 μm. Furthermore, the gas sensor element having each protective layer is used in this example because the protective layer is difficult to repel water and is therefore more suitable for the water coverage strength test.

[0109] like Fig.18As shown in FIG. 2 , the gas sensor element 2 is heated to 600°C by the heater 5, and a 1 μL water droplet W is dripped onto the tip of the element. Then, the initial value of the impedance value Zac of each gas sensor element is measured. Thereafter, the step of dripping a 1 μL water droplet W onto the tip of the element and measuring the impedance value Zac is repeated. The total amount of water droplets W dripped when the impedance value Zac changes by ±10% compared to the initial value is taken as the water coverage strength of the solid electrolyte. Fig.19 The results are shown in FIG. Fig.19 In the figure, the horizontal axis is Y2O3 / (ZrO2+Y2O3)mol%[%] in the entire cross section of the solid electrolyte, that is, the premise Y2O3 / (ZrO2+Y2O3)mol%[mol%], and the vertical axis is the water coverage strength (μL) of the solid electrolyte.

[0110] like Fig.19 As shown, if the pre-condition Y2O3 / (ZrO2+Y2O3)mol% is less than 3.5mol%, or greater than 6.9mol%, the water covering strength decreases. It is believed that this is because the difference in thermal expansion coefficient between the solid electrolyte and the electrode increases, and stress is generated relative to the temperature drop when covered with water, causing electrode peeling, etc. In contrast, when the pre-condition Y2O3 / (ZrO2+Y2O3)mol% is 3.5mol% or more and 6.9mol% or less, a higher water covering strength is obtained. It is believed that this is because the difference in thermal expansion coefficient between the solid electrolyte and the electrode is relatively small, and stress is difficult to generate relative to the temperature drop when covered with water, and it is difficult to cause electrode peeling, etc. In addition, it is also confirmed that when the pre-condition Y2O3 / (ZrO2+Y2O3)mol% is 3.5mol% or more and 6.9mol% or less, the water covering strength is 8μL or more, which is useful as a solid electrolyte for a cup-type gas sensor element requiring strength.

[0111] <Experimental Example 2> - Relationship between Y2O3 / (ZrO2+Y2O3)mol% in grains and phase transition -

[0112] For a point in a grain in the cross section of the solid electrolyte, SEM-EDX was used to measure Y2O3 / (ZrO2+Y2O3)mol% as described above, and then the crystalline phase was identified by EBSD (backscattered electron diffraction) for the same position. Furthermore, in this measurement, the cross section of the solid electrolyte was scratched with a diamond pen, the scratch and the grain boundary of the SEM image were used as marks, and a point in the grain not affected by the scratch was used as the measurement position. Then, the solid electrolyte was subjected to a thermal process of heating from 100°C to 950°C in 10 minutes and cooling from 950°C to 100°C in 10 minutes. Then, the crystalline phase was identified again by EBSD (backscattered electron diffraction) for the same position as above. This step was taken as 1 cycle and repeated 20 cycles.

[0113] As the EBSD device, a JSM-7900F manufactured by JEOL and attached to Symmetry manufactured by Oxford was used. At this time, the measurement conditions were set to an acceleration voltage of 20 kV, a measurement magnification of 10,000 times (10k), and a sample inclination of 70°. In addition, the crystal phases analyzed were set to M phase, C phase, and T phase of ZrO2.

[0114] Based on the above measurement results, the crystalline phase of the measurement site where Y2O3 / (ZrO2+Y2O3)mol% is 4mol% is as follows.

[0115] Initial stage: M phase, after 1 cycle: M phase, after 2 cycles: M phase, after 3 cycles: C phase or T phase, after 4 cycles: C phase or T phase, after 5 cycles: M phase, after 6 cycles: M phase, after 7 cycles: M phase, after 8 cycles: M phase, after 9 cycles: M phase, after 10 cycles: C phase or T phase, after 11 cycles: C phase or T phase, after 12 cycles: M phase, after 13 cycles: M phase, after 14 cycles: M phase, after 15 cycles: M phase, after 16 cycles: M phase, after 17 cycles: M phase, after 18 cycles: M phase, after 19 cycles: M phase, after 20 cycles: M phase

[0116] In this example, from the 2nd cycle to the 3rd cycle, the phase changes from the M phase to the C phase or the T phase, and from the 2nd cycle to the 3rd cycle, the phase changes from the C phase or the T phase to the M phase. In addition, from the 9th cycle to the 10th cycle, the phase changes from the M phase to the C phase or the T phase, and from the 11th cycle to the 12th cycle, the phase changes from the C phase or the T phase to the M phase. Therefore, the total number of phase changes that can be evaluated in this example is 4 times. Furthermore, there may also be a phase change between the C phase and the T phase. In EBSD, the crystal structures of the C phase and the T phase are very close and cannot be distinguished, but the volume change rate caused by the phase change between the C phase and the T phase is approximately 0, and no residual stress occurs, so the phase change can be ignored. In addition, since XRD, which is often used in the identification of crystalline phases, is a macroscopic evaluation method, the state of the phase change before and after the thermal process cannot be observed for individual grains.

[0117] The same test as above was carried out on the parts with different Y2O3 / (ZrO2+Y2O3)mol%, and the relationship between Y2O3 / (ZrO2+Y2O3)mol% and the total number of phase transitions was investigated. The results are shown in Table 1. Furthermore, the greater the total number of phase transitions, the more unstable the measurement area can be evaluated.

[0118] Table 1

[0119]

[0120] According to Table 1, it is confirmed that in the cross section of the solid electrolyte, the region where Y2O3 / (ZrO2+Y2O3)mol% is less than 3.3mol% and the region where it is more than 7mol% are stable regions where phase transition is difficult to occur through thermal cycling. In contrast, it is confirmed that in the cross section of the solid electrolyte, the region where Y2O3 / (ZrO2+Y2O3)mol% is more than 3.4mol% and less than 6.9mol% is an unstable region where phase transition is easy to occur through thermal cycling. As a result, it is found that the boundary between the stable phase and the unstable phase in the solid electrolyte at the operating temperature of the gas sensor can be determined by the Y2O3 / (ZrO2+Y2O3)mol% in the crystal phase.

[0121] <Experimental Example 3> - Relationship between the Total Area Ratio (A+B) [%] in the Solid Electrolyte and the Strength after Hot-Cold Cycle -

[0122] Similar to <Experimental Example 1>, solid electrolytes having different total area ratios (A+B) of 10% or more were prepared. The total area ratio (A+B) was changed by changing the pH adjustment of the slurry based on the addition of an alkaline solution, the firing time, and the firing temperature when preparing the gas sensor powder. In addition, in <Experimental Example 1>, a gas sensor powder for comparison was prepared without implementing the pH adjustment of the slurry based on the addition of an alkaline solution and the shaking for the purpose of agglomeration based on the collision of yttrium oxide particles. Using the gas sensor powder for comparison, solid electrolytes having a total area ratio (A+B) of less than 10% were prepared. Furthermore, in this example, the shape of the solid electrolyte was set to a plate-like body.

[0123] A sample with a width of 5 mm and a length of 45 mm was taken from each solid electrolyte. The sample was subjected to 1000 times of hot and cold cycles from room temperature to 950°C at a heating and cooling rate of ±950°C / 10 minutes. Then, a test piece for the 4-point bending strength test specified in JIS R1601 was taken from each sample after the hot and cold cycles, and each test piece was subjected to a 4-point bending strength test. Furthermore, the 4-point bending strength test was performed 10 times on each test piece. The 4-point bending strength of the test piece is the average value of the 10 4-point bending strength measurement values. Furthermore, the stacked gas sensor element preferably has a strength of 350 MPa or more, and the cup-type gas sensor element preferably has a strength of 400 MPa or more. Fig. 20 The above results are shown in FIG. Fig. 20 In the figure, the horizontal axis represents the total area ratio (A+B) [%] in the solid electrolyte, and the vertical axis represents the strength [MPa] of the solid electrolyte after thermal cycling.

[0124] like Fig. 20As shown, if the total area ratio (A+B) in the solid electrolyte is less than 10%, the strength of the solid electrolyte after the cold and hot cycle decreases. It is believed that this is because when the total area ratio (A+B) is less than 10%, the above-mentioned unstable region reaches more than 90%, so if the solid electrolyte is exposed to the cold and hot cycle, the crystal phase changes into a variety of crystal forms, and the stress formed by the phase change causes the inter-particle joints in the solid electrolyte to break, thereby reducing the strength. In contrast, as long as the total area ratio (A+B) in the solid electrolyte is more than 10%, the strength after the cold and hot cycle can be improved compared to when the total area ratio (A+B) is less than 10%. It is believed that this is because the ratio of the unstable region decreases and the ratio of the stable region increases, thereby reducing the stress formed by the phase change, slowing down the breakage of the inter-particle joints, and suppressing the decrease in strength.

[0125] In particular, when the total area ratio (A+B) in the solid electrolyte is 20% or more and 98% or less, the effect of suppressing the decrease in strength after the cold and hot cycle is high. It is believed that this is because the strength is sufficiently increased compared to the stress formed by the phase change according to the ratio of the unstable region and the stable region. When the total area ratio (A+B) in the solid electrolyte is 10% or more and less than 20%, or exceeds 98%, compared with the total area ratio (A+B) being less than 10%, although the strength after the cold and hot cycle can be sufficiently improved, there is a tendency for the strength after the cold and hot cycle to decrease somewhat compared with the total area ratio (A+B) being 20% ​​or more and 98% or less. Based on this result, it is believed that when the total area ratio (A+B) is 20% or more and 98% or less, it is suitable for use in cup-type gas sensor elements that require particularly high strength after the cold and hot cycle. Furthermore, when the total area ratio (A+B) in the solid electrolyte is 10% or more and less than 20% or exceeds 98%, it is considered to be suitable for a stacked gas sensor element that can use a solid electrolyte with lower strength than a cup-type gas sensor element.

[0126] <Experimental Example 4> - Relationship between the area ratio C [%] of aggregated particles with an aggregate particle size of 1 μm or more relative to the cross-sectional area of ​​granulated particles and the total area ratio (A + B) [%] in the solid electrolyte -

[0127] Similar to Experimental Example 1, a gas sensor powder having an area ratio C of agglomerated particles having an agglomerated particle diameter of 1 μm or more relative to the cross-sectional area of ​​the granulated particles in the cross section of the granulated particles in the range of 0.5% to 4%, a gas sensor powder having the area ratio C in the range of more than 0% to less than 4%, and a gas sensor powder having the area ratio C in the range of more than 4% were prepared. In addition, a gas sensor powder for comparison having the area ratio C of 0% was prepared similar to Experimental Example 3.

[0128] Using each gas sensor powder, each solid electrolyte was prepared in the same manner as in <Experimental Example 1>, and the total area ratio (A+B) [%] in each solid electrolyte was measured. Fig.21 The results are shown in FIG. Fig.21 In the graph, the horizontal axis represents the area ratio C [%] of aggregated particles having an aggregate particle size of 1 μm or more relative to the cross-sectional area of ​​granulated particles, and the vertical axis represents the total area ratio (A+B) [%] in the solid electrolyte.

[0129] like Fig.21 As shown, it is known that when the area ratio C of the agglomerated particles with an agglomerated particle size of 1 μm or more relative to the cross-sectional area of ​​the granulated particles is 0.5% or more and 4% or less, the total area ratio (A+B) in the solid electrolyte can be set to 20% or more and 98% or less. In addition, it is known that if the above-mentioned area ratio C exceeds 4%, the total area ratio (A+B) in the solid electrolyte becomes more than 98%. In addition, it is known that as long as the above-mentioned area ratio C exceeds 0%, that is, the granulated particles have agglomerated particles with an agglomerated particle size of 1 μm or more, the total area ratio (A+B) in the solid electrolyte can be set to 10% or more. Furthermore, it is known that when the above-mentioned area ratio C is 0%, that is, the granulated particles do not have agglomerated particles with an agglomerated particle size of 1 μm or more, it is difficult to set the total area ratio (A+B) in the solid electrolyte to 10% or more.

[0130] <Experimental Example 5> - Relationship between the pH value in the slurry pH adjustment step and the area ratio C [%] of the cross-sectional area of ​​the aggregated particles having an aggregate particle size of 1 μm or more relative to the granulated particles -

[0131] A plurality of gas sensor powders were prepared in the same manner as in <Experimental Example 1>. However, in this example, the pH of the slurry was set to a range of 9 to 12 by adjusting the amount of ammonia water added. For the obtained gas sensor powders, the area ratio C [%] of the aggregated particles having an aggregated particle size of 1 μm or more relative to the cross-sectional area of ​​the granulated particles was measured. Fig. 22 The results are shown in FIG. Fig. 22 In the graph, the horizontal axis represents the pH value in the slurry pH adjustment step, and the vertical axis represents the area ratio C [%] of the aggregated particles having an aggregated particle size of 1 μm or more to the cross-sectional area of ​​the granulated particles.

[0132] like Fig. 22 As shown, it is found that when the pH value in the slurry pH adjustment step is set to a range of 10 to 12, the area ratio C of aggregated particles having an aggregate particle size of 1 μm or more to the cross-sectional area of ​​granulated particles can be set to a range of 0.5% to 4.5%.

[0133] The present disclosure is not limited to the above-mentioned embodiments and experimental examples, and various changes can be made within the scope of the main purpose. In other words, although the present disclosure is described based on the embodiments, it should be understood that the present disclosure is not limited to the embodiments and structures. The present disclosure also includes various modifications and variations within the scope of equality. Moreover, various combinations and methods, and other combinations and methods including only one element, elements above it, or elements below it, are also included in the scope or thought of the present disclosure.

Claims

1. A gas sensor (1), comprising a solid electrolyte (21) composed of zirconium oxide containing yttria, wherein: The solid electrolyte contains a T phase, The mol% of Y2O3 relative to the total of ZrO2 and Y2O3 in the solid electrolyte as a whole is 3.5 mol% or more and 6.9 mol% or less, In the cross-section of the solid electrolyte, when the area ratio of the region (211) in which the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 is less than 3.3 mol% is set to A% relative to the entire cross-section, and the area ratio of the region (212) in which the mol% of Y2O3 relative to the total of ZrO2 and Y2O3 is greater than 7 mol% and contains the T phase is set to B% relative to the entire cross-section, the total of A% and B%, that is, the total area ratio, is greater than 10% and less than 98%.

2. The gas sensor according to claim 1, wherein: The total area ratio is 20% or more and 98% or less.

3. A gas sensor powder (6), comprising granulated particles (60) comprising a plurality of zirconium oxide particles (61) and a plurality of yttrium oxide particles (62), wherein: In the granulated particles, The mol% of Y2O3 relative to the total of ZrO2 and Y2O3 is 3.5 mol% or more and 6.9 mol% or less, having agglomerated particles (620) formed by agglomerating the yttrium oxide particles, The agglomerated particles have an agglomerated particle size of 1 μm or more and 15 μm or less. In the cross section of the granulated particle, an area ratio of the aggregated particles having an aggregate particle size of 1 μm or more and 15 μm or less relative to the cross-sectional area of ​​the granulated particle is 0.5% or more and 4% or less.

4. The gas sensor powder according to claim 3, wherein The granulated particles include the aggregated particles having an aggregated particle size of 2 μm or more and 15 μm or less.

Citation Information

Patent Citations

  • Solid electrolyte

    JP1981042909A

  • Article management system and method

    JP2019219911A

  • Advanced solid electrolyte and method of fabrication

    CN106058288A

  • Zirconia structure and its manufacturing method

    JP2006023128A